The Influence of School Learning Media on Students' Learning Motivation (Survey Study at SMP Islam Terpadu Anugerah Insani) - Afwah, Raden; Ratnandari, Luluk Dwi; Hakim, Ibrahim; Syahrullah, Syahrullah; Hastuti, Saptiyani; Afifah, Afifah (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This research endeavor seeks to elucidate the influence of pedagogical media utilization on the learning motivation of students. Employing a correlational descriptive analytic methodology, the study was conducted at SMP IT Anugerah Insani, targeting a population of 331 students, while the accessible population comprised 108 individuals. A sample of 85 students was derived, adhering to a 5% margin of error. The sampling technique employed was Slovin’s formula. The findings revealed an rxy coefficient of 0.500, situated within the interval of 0.40to 0.70. In accordance with the product-moment correlation index, this donotes a moderate correlation between variables X and Y.